Early-Claim Modifiable Factors Associated With Return-to-Work Self-Efficacy Among Workers Injured at Work: Are There Differences Between Psychological and Musculoskeletal Injuries?. Issue 12 (December 2017) - Black, Oliver; Sim, Malcolm R.; Collie, Alexander; Smith, Peter
Abstract : Objective: The objective of this study was to investigate modifiable early-injury factors which are associated with self-efficacy to return-to-work (RTW-SE) and explore whether these factors are different for people with psychological or upper-body musculoskeletal (UB-MSK) injuries. Methods: The study used a sample of workers with a UB-MSK ( N = 244) or psychological ( N = 113) injury who were off work. Differences between injury types were investigated across variables related to: (1) communication with RTW stakeholders; and (2) components of the job itself. A stratified and multigroup analysis was conducted using structural equation modeling (SEM). Results: Injury-stratified models revealed no significant differences. In a combined model, higher job autonomy and low-stress contact from the RTW coordinator remained significantly associated with higher RTW-SE. Conclusions: Job autonomy and low-stress contact from the RTW coordinator are possible areas to target to increase self-efficacy among injured workers.